A new species of Tarenna (Rubiaceae: Ixoroideae) from Kerala, India - Jose, Robi Aloor; Balan, Anoop Puthuparambil; Ponnachan, Thomas Valukattil (Phytotaxa, 2024)
A new species of Tarenna Gaertn. (Rubiaceae), T. idukkiana Robi & Balan sp. nov. from the Cardamom Hill Reserves of Elappara, Idukki district, Kerala, India is described here. A detailed description along with diagnostic characters between allied species, pollen morphology and colour photographs are provided.